A KCNC1 variant linked to Rett syndrome disrupts ER to Golgi trafficking of Kv3.1 channel - Diego Maureira; Carla Rubilar; Joaquín López; Paola Santander; Hans Moldenhauer; Ian Silva; Pablo Cruz; Denise Riquelme; Javiera Baeza; Wendy González; Patricio Orio; Evrim Servili; et al. (Proceedings of the National Academy of Sciences, 2026)
Intrinsic neuronal excitability, defined by the balance between input and output signals, is crucial to neural function, and its disruption underlies various neurological diseases. Kv3.1 channels, encoded by KCNC1 , are essential for high-frequency action potential firing. Variants in these channels are associated with several subtypes of epilepsy. We report a patient with developmental regression and epilepsy, meeting Rett syndrome criteria, who carries a KCNC1 variant encoding the S474C substitution in Kv3.1 (Kv3.1 S474C ). Electrophysiological and biochemical assays reveal that Kv3.1 S474C reduces channel presence in the plasma membrane and is retained in the endoplasmic reticulum. In murine primary cortical neuron cultures expressing Kv3.1 S474C , we observed reduced neuronal firing frequency and exclusion of the channel from the axon initial segment. Consistently, we found a decreased firing frequency using a conductance-based computational neuronal model. In summary, this study identifies a link between a KCNC1 variant and Rett syndrome, highlighting the importance of S474 residue in Kv3.1 channel trafficking and function in neurons.